Controlling the harmonic generation in transition metal dichalcogenides and their heterostructures - Zhou Renlong; Krasnok Alex; Hussain Naveed; Yang Sa; Ullah Kaleem (Nanophotonics, 2022)
The growing interest in transition metal dichalcogenides (TMDs) has encouraged researchers to focus on their nonlinear optical properties, such as harmonic generation (HG), which has potential for fundamental science and applications. HG is a nonlinear phenomenon used to study low-dimensional physics and has applications in bioimaging, optical signal processing, and novel coherent light sources. In this review, we present the state-of-the-art advances of HG in atomically-thin TMDs and their heterostructures. Different factors affecting the HG in TMDs such as strain, electric gating, excitonic resonance, phase and edge modulation, and valley-induced HG are discussed with a particular emphasis on the HG in heterostructure van der Waals TMDs. Moreover, we discuss the enhancement of HG in TMDs by incorporating cavities and nanostructures including the bound states in the continuum with extreme Q-factor. This work provides a concise summary of recent progress in engineering HG in atomically-thin TMDs and their heterostructures and a compact reference for researchers entering the field.